THE ROLE OF AL AZHAR MEDAN'S LEADING HIGH SCHOOL IN STRENGTHENING DIGITAL LITERACY FOR ADOLESCENT MENTAL HEALTH - Yuri Prameswari; Galu Relung Wangi; Fakhri Rozy; Adam Al Hafizh; Rifky Hadi; Ayu Astuti (PT. Radja Intercontinental Publishing, 2025)
This study aims to analyze the role of Al Azhar Medan's flagship high school in strengthening students' digital literacy as an effort to maintain adolescent mental health in the digital era. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results show that the school has a strong commitment to building a culture of digital literacy through the integration of technology into learning, training for teachers, and the formation of a student digital community. Digital literacy is not only understood as technical skills, but also includes ethics, responsibility, and reflective awareness of the impact of social media on psychological well-being. Increased digital literacy has been shown to contribute to reducing levels of stress, anxiety, and social pressure experienced by students. The school implements educational, collaborative, and preventive strategies through programs such as digital well-being seminars, Islamic digital ethics training, and thematic counseling. Challenges faced include limited learning time and the gap in digital skills among students, but these can be overcome through mentoring and collaboration between teachers, students, and parents. This study confirms that strengthening digital literacy plays a crucial role in shaping adolescent character that is resilient, mentally healthy, and responsible in using technology.